Bifid mandibular canals and their cortex thicknesses: A comparison study on images obtained from cone-beam and multislice computed tomography - E-Chin Shen; Earl Fu; Michelle Peng; Yao-Dung Hsieh; Hsiao-Pei Tu; Min-Wen Fu (Elsevier, 2016)
Background/purpose: High prevalence of bifid mandibular canals has been visualized with various types of computerized tomography (CT). Along the canals, a various ranged corticalization was recently reported. The depiction of the fine anatomic structures on multislice and cone-beam CT images was compared. Material and methods: The presence or absence of the bifid canal was assessed on 327 images obtained by multislice CT (MSCT; n = 173) or by cone-beam CT (CBCT; n = 154), according to the configuration. The cortex thickness and distribution were also assessed. Results: The prevalence of bifid canal detected by CBCT was significantly greater than that detected by MSCT (42.2% vs. 18.7% for hemi-mandibles and 58.4% vs. 30.6% for patients). Cortical thickness recorded by CBCT was significantly thinner than that recorded by MSCT (0.48 mm vs. 0.65 mm, P < 0.001); however, the distributions of corticalization detected by the two tomography methods were similar. There was a significant association of cortex thickness with CT type and corticalization degree (R2 = 0.530, P < 0.001). Conclusion: Thinner cortices, but greater prevalence of bifid canals recorded by CBCT, compared to MSCT, suggests that clinicians should be cautious when using CT to interpret this fine anatomic structure.